The mists of Avalon - Bradley, Marion Zimmer (Ballantine, 1984)
When Morgan le Fay (Morgaine) has to sacrifice her virginity during fertility rites, the man who impregnates her is her younger brother Arthur, whom she turns against when she thinks he has betrayed the old religion of Avalon.